Effect of Type of Diluent on The Growth of Bacterial Colonies Bacillus sp. on The Isolation Process in Bacterial Culture - Darmawan, Riko; Wirawan, Indra; Agustini, Maria (Hasanuddin University, 2025)
Bacillus sp. are bacteria that play an important role in shrimp farming, especially in maintaining the balance of the pond ecosystem and as probiotics. This study aims to determine the effect of the type of diluent on the number of Bacillus sp. colonies formed in the isolation process and determine the most effective diluent. Three types of diluents were used, namely distilled water, NaCl solution, and infusion water (NaCl 0.9%). This study used a completely randomized design (CRD) with 9 replicates in each treatment. The data obtained were analyzed using one-way ANOVA to determine the significance of differences between treatments, followed by Tukey test and LSD 5%. The results showed that distilled water produced the highest number of colonies (1711.56), followed by infusion water (1222) and NaCl solution (771.44). The ANOVA test showed highly significant differences (p<0.05) between treatments, with Tukey and LSD 5% test results supporting these findings. 0.9% infused water was proven to be an effective diluent for the isolation of Bacillus sp. which provides an accurate picture of the bacterial population, because growth is optimal and remains controlled. This study recommends the use of infusion solution in the process of bacterial isolation to be applied in pond culture, in order to improve water quality through the utilization of probiotic bacteria.